2016
DOI: 10.1002/jmri.25422
|View full text |Cite
|
Sign up to set email alerts
|

Uterine junctional zone thickness in infertile women evaluated by MRI

Abstract: 1 J. Magn. Reson. Imaging 2017;45:926-936.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The rate of miscarriages at 12 weeks or later tended to be particularly high in the advanced group. Several previous studies have reported that the association between adenomyosis and infertility was stronger in patients with JZ or myometrium thickness, which are considered signs of adenomyosis progression [23,32,33]. Moreover, adenomyosis is associated with late miscarriage and preterm labour in patients with impaired deep placentation, which is defined by the presence of abnormalities of the JZ, involved in implantation, and absent or incomplete remodelling of the JZ segment of the spiral arteries [34,35].…”
Section: Discussionmentioning
confidence: 98%
“…The rate of miscarriages at 12 weeks or later tended to be particularly high in the advanced group. Several previous studies have reported that the association between adenomyosis and infertility was stronger in patients with JZ or myometrium thickness, which are considered signs of adenomyosis progression [23,32,33]. Moreover, adenomyosis is associated with late miscarriage and preterm labour in patients with impaired deep placentation, which is defined by the presence of abnormalities of the JZ, involved in implantation, and absent or incomplete remodelling of the JZ segment of the spiral arteries [34,35].…”
Section: Discussionmentioning
confidence: 98%
“…Because the propagated contraction of the myometrium in a nonpregnant uterus originates from the junctional zone, a thickened junctional zone would affect the contractility of the uterus and hinder the transportation of sperm and embryo implantation. Thickening of the junctional zone has been known to be a predictive factor of infertility and embryo implantation failure 19,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…2). 19 These parameters were measured 3 times, and the averaged value was set as the final value. The final JZT was defined as the average value of the JZT of the anterior wall, posterior wall, and fundus.…”
Section: Methodsmentioning
confidence: 99%
“…An endometrial biopsy can examine the endometrium at the histological level [5], but it is an invasive method with a high incidence of complications and is not widely accepted in clinical practice. Magnetic resonance imaging has certain advantages in clarifying the thickness of the endometrium and its relationship with the myometrium [6], but the investigation is expensive and time-consuming. Ultrasound is widely used in clinical practice because of its convenience, non-invasiveness, and low cost.…”
Section: Introductionmentioning
confidence: 99%